2000
DOI: 10.12693/aphyspola.98.561
|View full text |Cite
|
Sign up to set email alerts
|

EPR Investigations of Model Neuromelanins

Abstract: The aim of this work was to compare free radical properties of some model neuromelanins obtained from dopamine and its mixture with 5-S-cysteinyldopamine in various molar ratios. The EPR method was used in these investigations; the samples were detected at X and K bands. The parameters of EPR spectra, free radicals concentrations in air and in vacuum, the influence of microwave power and temperature on intensity of resonance signals were measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
3
0
0
Order By: Relevance
“…The following fitting parameters were used: g x = g y = 2.0038 and g z = 2.00125 with peak-to-peak line widths ΔB x,y = 0.4 mT and ΔB z = 0.485 mT (EasySpin 53−55 ). The normalized integral intensity increases with a decrease of temperature but less than expected for , where C = 41.6 ± 2.8 and T c = −4.63 ± 0.63 (R 2 = 0.9868, Figure 3c), and is similar to the results reported by Skrzypek, 56 which was explained by semiconductor properties and trapping of charge carriers. Goncalves et al showed that heating above 60 °C (48 h) decreases the conductivity by 3 orders of magnitude and increases the spin density by a factor of 3, which is a reversible process.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The following fitting parameters were used: g x = g y = 2.0038 and g z = 2.00125 with peak-to-peak line widths ΔB x,y = 0.4 mT and ΔB z = 0.485 mT (EasySpin 53−55 ). The normalized integral intensity increases with a decrease of temperature but less than expected for , where C = 41.6 ± 2.8 and T c = −4.63 ± 0.63 (R 2 = 0.9868, Figure 3c), and is similar to the results reported by Skrzypek, 56 which was explained by semiconductor properties and trapping of charge carriers. Goncalves et al showed that heating above 60 °C (48 h) decreases the conductivity by 3 orders of magnitude and increases the spin density by a factor of 3, which is a reversible process.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…The normalized integral intensity increases with a decrease of temperature but less than expected for noninteracting localized paramagnetic centers described by the Curie function with the relation ∼ T –1 (1 at 300 K and 60 at 5 K), which suggests that the delocalization over aromatic ring π-electrons and localized radicals coexist in this system (Figure c). Magnetic susceptibility can be described by the Curie–Weiss function , where C = 41.6 ± 2.8 and T c = −4.63 ± 0.63 ( R 2 = 0.9868, Figure c), and is similar to the results reported by Skrzypek, which was explained by semiconductor properties and trapping of charge carriers. Gonçalves et al showed that heating above 60 °C (48 h) decreases the conductivity by 3 orders of magnitude and increases the spin density by a factor of 3, which is a reversible process .…”
Section: Results and Discussionsupporting
confidence: 86%
“…The results observed for natural and synthetic melanin reported in the work of Blois indicate that the magnetic susceptibility obeys the Curie low in broad temperature range. Our results are similar to those obtained by Skrzypek, where magnetic susceptibility is weakly dependent on temperature. This behavior was explained by the appearance of thermally activated radicals.…”
Section: Spectroscopysupporting
confidence: 92%
“…Por exemplo, medidas de EPR 1 mostram a existência de pelo menos um spin desemparelhado por cada 100 a 200 unidades monoméricas [16]. Estudos recentes [17] nesta direção aplicados para a substância negra do cérebro, têm permitido mostrar que ali existe além de eumelaninas, também feomelaninas, podendo conhecer em que proporção se encontram as populações de cada uma. O uso de raios X sobre melaninas com diferentes origens [18] não revela nenhum tipo de estrutura em particular, apresentando picos pouco definidos.…”
Section: Capítulo 1 Introduçãounclassified